(untitled) (Journal of Physical Education (Maringá), 2019)
This study analyzed the association between physical activity, health status and life quality among women with fibromyalgia. Cross-sectional study based on the clinical information of 177 women (42.1 ± 8.6 years old) diagnosed with fibromyalgia and assisted in rheumatology clinics of the private sector of the Unified Health System (UHS) in the city of Maringá-PR, Brazil. The instruments were the International Physical Activity Questionnaire (IPAQ), the Fibromyalgia Impact Questionnaire (FIQ) and the WHOQOL-Bref. Data analysis was conducted through Mann-Whitney test, Spearman correlation and Structural Equation Analysis (p<0.05). Results showed positive correlations between physical activity and life quality domain. Health status showed negative correlation life quality domains. Structural Equation Analysis revealed days of walking per week showed positive association with life quality domains. Model 3 showed that the impact of fibromyalgia on the health status showed a moderate negative association with life quality domains. It was concluded that physical activity, specifically walking, represents a positive factor for the life quality of women with fibromyalgia, since the disease was negatively associated with life quality, while physical activities presented a positive relation with life quality.